Sauropod Trackway Morphometrics: An Exploratory Study Using Highway A16 Excavation at the Courtedoux-Tchâfouè Track Site (Late Jurassic, NW Switzerland) - Sciscio, Lara; Belvedere, Matteo; Meyer, Christian A.; Marty, Daniel (Frontiers in Earth Science, 2022)
Ichnogeneric classification of sauropod trackways is determined using qualitative and quantitative descriptions of morphological parameters. More recently, the validity of several of these parameters has been called into question (e.g., trackway gauge). This paper aims to test traditional and more novel landmark-based geometric morphometric (GM) analysis to describe sauropod tracks and trackways. The Courtedoux-Tchâfouè (TCH) tracksite, in NW Switzerland, has been used as a test site because it hosted several Late Jurassic sauropod track-bearing levels, over a short time period (~ 40ka), creating a time capsule of sauropod activity. Exploratory statistical analyses suggest that the TCH trackway dataset can be partitioned into clusters based on trackway parameters (e.g., width of pes angulation pattern/pes length) that demonstrate differences between trackways. Nevertheless, clustering reflected a moderate degree of intercluster similarity and a continuum in TCH trackway morphologies. The GM analysis of TCH pes impressions, from several trackways, indicates a similar morphotype and did not significantly differentiate pes tracks from various stratigraphic levels. Currently, the results indicate that neither linear nor landmark-based geometric morphometric methods strongly segregate tracks at TCH nor show a time-control (i.e., via stratigraphic level) over the short interval studied. The methods reinforce that sauropod pes impression shape is conservative and that combining morphological methods to be inclusive of sauropod trackway data is important. The TCH site demonstrates that variability may reflect morphological continuums and behavioural factors and does not unambiguously differentiate unique sauropod trackmakers. More exploration on the minimum number of trackway parameters as predictors of sauropod ichnotaxonomy is needed. Integrating complementary techniques will provide more insight and practical means of identification and delineation of sauropod tracks and their trackways.